2021
DOI: 10.1111/and.14162
|View full text |Cite
|
Sign up to set email alerts
|

Smoking status and the baseline international index of erectile function score can predict satisfactory response to platelet‐rich plasma in patients with erectile dysfunction: A prospective pilot study

Abstract: Erectile dysfunction (ED) is a common condition with a significant impact on the quality of life. Regenerative medicine maladies are intended to repair or replace damaged tissues and organs through different therapeutic mechanisms. Our aim was to study the effect of intra‐corporeal injection (ICI) of platelet‐rich plasma (PRP) in ED patients. Thirty‐four patients’ erectile function was evaluated by filling up an abridged form of the international index of erectile function (IIEF‐5) before and after PRP therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
14
0
2
Order By: Relevance
“…(2021) reported that cavernous PRP therapy in ED cases is reliable but although the mean IIEF‐EF scores were significantly increased, the ED grades were the same. Moreover, Zaghloul et al (2021) demonstrated that cavernous PRP injection for ED patients could be a encouraging modality where baseline IIEF‐5 and smoking status were predictors for such satisfactory reaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2021) reported that cavernous PRP therapy in ED cases is reliable but although the mean IIEF‐EF scores were significantly increased, the ED grades were the same. Moreover, Zaghloul et al (2021) demonstrated that cavernous PRP injection for ED patients could be a encouraging modality where baseline IIEF‐5 and smoking status were predictors for such satisfactory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…ICI was carried out over 4 injection points, 2 on each side of the penis (one in the proximal third and one in the middle third) using a 5/16 inch 28G needle (Figure 1) followed by applied pressure to the injection site and the root of the penis for 1–2 min to avoid rapid washout of the material. Massage of the penis was carried out for 1–2 min to distribute the material into the penis (Zaghloul et al, 2021). Both groups were given a daily dose of 5 mg tadalafil plus vardenafil 20 mg on demand during the entire study. All cases were evaluated at baseline, and 12 weeks after PRP injections by: IIEF‐5 Questionnaire no (ED [total score, 22–25], mild ED [17–21], mild‐moderate ED [12–16], moderate ED [8–11] and severe ED [5–7]) (Cappelleri & Rosen, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zaghlou et al examined the effects of smoking status and baseline IIEF5 in the response to PRP ( 39 ). The study was aimed to evaluate the effect of PRP ICI in men with ED whose ED was not responsive to PDE5i oral medication (including daily and on-demand regimes).…”
Section: Review Of the Current Evidencementioning
confidence: 99%